Advancing sustainable food preservation: Ultrasound and thermosonication as novel approaches to enhance nutritional and bioactive properties of broccoli juice - Seydi Yıkmış; Melikenur Türkol; Dilek Dülger Altıner; Aylin Duman Altan; Kübra Sağlam; Gholamreza Abdi; Nazlı Tokatlı; Güler Çelik; Rana Muhammad Aadil (Food Chemistry: X)
To meet the challenges of sustainability and nutritional quality, innovative food processing technologies are essential. This study investigates the application of ultrasound and thermosonication- emerging non-thermal preservation techniques- to improve the functional properties of broccoli juice. Using Response Surface Methodology (RSM) and Adaptive Neuro-Fuzzy Inference System (ANFIS), the processes were optimised to maximize chlorophyll and ascorbic acid content. Optimal ultrasound parameters (4 min, 91.1 % amplitude) achieved 12.29 mg/100 mL chlorophyll and 79.38 mg/100 g ascorbic acid. Thermosonication (6.9 min, 66 % amplitude, 40 °C) gave comparable results. Both treatments significantly improved phenolic composition and mineral content, demonstrating superior preservation of bioactive compounds and reduced nutrient degradation compared to traditional methods. The results highlight the potential of ultrasound and thermosonication for sustainable food systems by improving nutritional quality and shelf life, thereby contributing to reduced food waste and environmentally friendly processing. This research provides valuable insights into the integration of non-thermal technologies in the production of functional beverages, supporting the development of circular food systems and sustainable innovation.